Histochemical Studies Of Carbohydrates, Acid Mucopoly Saccharides And Proteins In The Trachea Of Black Bengal Goat (Capra Hircus) (Applied Biological Research, 2011)
Histochemical studies of carbohydrates and proteins were conducted on  the trachea of ten adult healthy Black Bengal goats (Capra hircus) of  either sex. The goblet cells, tracheal glands and tracheal cartilages  manifested intense positive reactions generally for carbohydrates,  whereas connective tissue and muscle fibres were weak to moderately  positive for these constituents. The epithelium, glands, cartilage matrix,  perichondrium and muscle layers manifested strong reactions for acid  mucopolysaccharides. Reaction for proteins was strong to intense in the  epithelium, glands, perichondrium and muscle fibres, whereas other  structures showed only weak or moderate reaction.
Keywords: Acid mucopolysaccharides; Black Bengal goat; carbohydrates; histochemistry; proteins; trachea